2021
DOI: 10.1128/jcm.00936-21
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Sensitive Real-Time PCR Detection of Major Antiviral-Drug Resistance Mutations in Chronic Hepatitis B Patients by Use of a Predesigned Panel of Locked-Nucleic-Acid TaqMan Probes

Abstract: We developed a novel real-time PCR assay that simultaneously evaluates eleven major nucleos(t)ide antiviral (NA) drug-resistance mutations (mt) in chronic hepatitis B patients (CHB), including L180M, M204I/V, and V207M (lamivudine (LMV) resistance), N/H238A/T (Adefovir (ADF) resistance) which are circulating in Vietnam; T184G/L, S202I, M250V (entecavir (ETV) resistance), and A194T (tenofovir resistance) which have been recently reported in several studies across the globe. We detected drug-resistant mt in HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, the 16S rRNA gene of each isolate was sequenced, and an internal control was performed for all possible isolates. The real-time PCR method enabled the discrimination of members of the genus Vibrio in less than 4 h. LNA probes offer significant advantages such as high sensitivity, a wide linear range, a clinically relevant detection limit, ease of design, and improved signal generation [46,47]. LNA probes have the ability to distinguish single-base mutations through amplification curves without the need for complex detection or additional Tm analysis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 16S rRNA gene of each isolate was sequenced, and an internal control was performed for all possible isolates. The real-time PCR method enabled the discrimination of members of the genus Vibrio in less than 4 h. LNA probes offer significant advantages such as high sensitivity, a wide linear range, a clinically relevant detection limit, ease of design, and improved signal generation [46,47]. LNA probes have the ability to distinguish single-base mutations through amplification curves without the need for complex detection or additional Tm analysis [48].…”
Section: Discussionmentioning
confidence: 99%
“…LNA-based RT-PCR assays have been widely applied to viral single-nucleotide polymorphism analysis as well as simple viral detection in clinical settings instead of the less sensitive traditional RT-PCR or nested RT-PCR assays prone that are to cross-contamination[ 31 , 32 ]. In particular, it has recently been reported that this method could successfully identify YMDD mutations of HBV from Korean patients with chronic HBV infections[ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides savings due to faster discharge and less wasteful drug administration, POC-PCR does not require additional qualified personnel. Therefore, nucleic acid analysis with these methods can be carried out by personnel with minimal training, although the advantages of such tests can be influenced by the work technique, especially by delaying testing, which inherently leads to delaying appropriate treatment [32,86,131].…”
Section: Classic Pcr-poc Pcr Comparisonmentioning
confidence: 99%